Common Disturbing Ocular Issue: Dry Eye Syndrome Due to the Overuse of Digital Screens - Karaarslan, Cuneyt; Coskun, Arzu (Disease and Health Research: New Insights Vol. 5, 2024)
The excessive and prolonged use of electronic devices with digital screens may cause some serious health problems. The ocular surface problems particularly Dry Eye Syndrome may be the most common and preventable conditions affecting the eyes. In this study, the unfavourable and potentially harmful effects of digital screens on the lacrimal system and tear functions were evaluated in 221 participants. Their ocular surface conditions were evaluated by Ocular Surface Disease Index (OSDI) scores and their lacrimal functioning was measured by Schirmer’s test. A reciprocal and statistically significant relationship was found between dry eye symptoms and OSDI scores. This relationship was more prominent, especially in long-duration use of smartphones with brighter background lights.